2012
DOI: 10.4269/ajtmh.2012.11-0476
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Single Oral Dose of Oxfendazole against Fasciola hepatica in Naturally Infected Sheep

Abstract: Abstract. The efficacy of a single oral dose of 30 mg/kg of oxfendazole against Fasciola hepatica was evaluated in a controlled study in naturally infected sheep. Sheep were diagnosed by stool microscopy after sedimentation, and positive animals were randomized to oxfendazole (N = 20) or no treatment (N = 20).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…At this stage, their activity was evaluated alongside commercial drugs, three BZs (TCBZ, OXF, and ABZSO) and CLR, at a concentration of 5 µM, to compare their activities. While OXF has demonstrated in vitro and in vivo properties, it is not currently a recommended flukicide, in contrast to ABZSO, TCBZ, and CLR [ 55 , 56 ]. When performing the EHT on a susceptible F. hepatica isolate at 5 µM, all hit compounds showed activities exceeding 71%, with BZD56 being the most potent one, displaying an activity slightly below 90%.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, their activity was evaluated alongside commercial drugs, three BZs (TCBZ, OXF, and ABZSO) and CLR, at a concentration of 5 µM, to compare their activities. While OXF has demonstrated in vitro and in vivo properties, it is not currently a recommended flukicide, in contrast to ABZSO, TCBZ, and CLR [ 55 , 56 ]. When performing the EHT on a susceptible F. hepatica isolate at 5 µM, all hit compounds showed activities exceeding 71%, with BZD56 being the most potent one, displaying an activity slightly below 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Of the several strategies for the control of bovine fasciolosis described, in practice usually strategic anthelmintic control is used with flukicide treatment time and interval depending on the climatic zone (Armour, 1975;Boray, 1971Boray, , 1972Harris and Charleston, 1971;Schneider et al, 1975;Torgerson and Claxton, 1999;Whitehead, 1976). A variety of fasciolicides is available for the treatment of bovine fasiolosis: triclabendazole, albendazole, oxyclozanide, clorsulon, nitroxynil, rafoxanide or oxfendazole (Fairweather, 2011;Gomez-Puerta et al, 2012;Martínez-Valladares et al, 2010). Of all these agents, triclabendazole is the most effective against immature stages of the parasite, which makes it the drug of choice for the treatment of acute fasciolosis, which is more commonly seen in sheep than in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…(26) In a masked, controlled study, our group has also demonstrated that a single oral dose of 30 mg/kg of OXF was fully effective against Fasciola hepatica in naturally infected sheep (n=20) compared to no cure at all in untreated animals (n=20); no side effects were discernible in the OXF treated animals. (27)…”
Section: Introductionmentioning
confidence: 99%